A novel capacitive RF-MEMS switch for multi-frequency operation. (September 2019) - Angira, Mahesh; Bansal, Deepak; Kumar, Prem; Mehta, Khusbu; Rangra, Kamaljit
Abstract: This paper reports a novel capacitive RF-MEMS switch. The presented device has frequency reconfigurable characteristics and thus can be used in multi-band wireless systems. The switch is realized through two non-uniform cantilevers with dissimilar shape. The structure of the cantilevers is kept dissimilar to achieve the different value of inductance in the down-state of the device and hence the different electrical resonant frequency. Further, the proposed device has also overcome issue of shift in the isolation response caused by residual stress in switching structure and micro-roughness in the deposited SiO2 layer. The device forms a M-I-M capacitor at the central conductor of the transmission line to resolve the above cited problem and also allows the use of cantilever structures for the implementation of capacitive switches in place of conventional bridge type structures. The measured isolation response shows three optimum values of 25.40 dB, 20.44 dB, and 30.80 dB at 9.4 GHz, 11.6 GHz, and 25.2 GHz respectively. The measured insertion loss is also better than 0.41 dB up to 30 GHz. Under, mechanical characterization, cantilever with two narrow beams shows resonant frequency of 3.90 kHz and cantilever with single narrow beam shows resonant frequency of 4.66 kHz. Furthermore, the device has measured pull-in voltage which is less than 16 V. Highlights: This paper presents a true frequency reconfigurable capacitive shunt RF-MEMS switch. The device is realized using non-uniform cantilevers. This is the first time a capacitive switch has been realized through a cantilever structure. The device shows multiple isolation peaks in different frequency bands. The device is fabricated using surface micro-machining process. The measured RF response of the device confirms its frequency reconfigurable nature. The device has maximum pull-in voltage of 15 V (measured value) and mechanical resonant frequency of 4.66 kHz.